Can AI Detect Pneumonia on X-rays? A Deep Dive into Diagnostic Accuracy and Clinical Integration - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2024)
Can AI Detect Pneumonia on X-rays? A Deep Dive into Diagnostic Accuracy and Clinical Integration The integration of Artificial Intelligence (AI) into me...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation; Machine Learning